Virtual Times and Possible Worlds: the Madness of the Real - Longo, Anna (Scenari, 2021)
This paper compares Gilles Deleuze’s and Quentin Meillassoux’s strategies for overcoming Kant’s a priori limitation of possible experience. The former aims to account for the genesis of new concepts, while the latter aims to account for the impossibility of grounding them on any efficient cause. We will see that these two strategies depend on different mathematical backgrounds – analytical geometry and set theory – and that each of them implies a particular notion of the virtual.